Avaliação da atividade de ectonucleotidases no córtex cerebral e plaquetas de ratos expostos à fumaça de cigarro - Thomé, Gustavo Roberto (2009)
Inflammatory and degenerative pathophysiological processes within the central nervous system (CNS) and platelets are important causes of human disease promoted by cigarette smoke. The objective of the present study was to evaluate activity of the enzymes that hydrolyze nucleotides and nucleosides in synaptosomes of cerebral cortex and platelets from rats exposed to aged and sidestream diluted smoke of commercial cigarettes. The animals were randomly divided into two groups (ten rats in each group): control (not exposed to cigarette smoke) and smoke (exposed to cigarette smoke). The smoke group was exposed via inhalation through the nose only 15 minutes per day inside a cigarette smoke exposure chamber during 3 weeks. The results demonstrated that E-NTPDase (with ATP and ADP as substrate) activity was significantly higher in the smoke group (p<0.05), while the 5'- nucleotidase with AMP as substrate demonstrated decreased activity in the smoke group (p<0.05). However, in platelets activities demonstrated that E-NPP and ENTPDase with ATP as substrate and 5´-nucleotidase with AMP as substrate were significantly higher in the smoke group (p<0.05) as compared to the control group, while E-NTPDase with ADP as substrate demonstrated decreased activity in the smoke group (p<0.05). A decrease of adenosine, a neuroprotective nucleoside, was observed in brain, which could lead to damage of the brain tissue. However, in platelets, there was an increase of adenosine, which may reflect adaptative changes. These alterations caused by cigarette smoke on ectonucleotidase activities may assist in verifying pathophysiological effects in biological systems.